1993
DOI: 10.1084/jem.178.3.1023
|View full text |Cite
|
Sign up to set email alerts
|

The bone marrow of multiple myeloma patients contains B cell populations at different stages of differentiation that are clonally related to the malignant plasma cell.

Abstract: Suml-nal'~One of the distinguishing features of multiple myeloma (MM) is the proliferation of a clonal plasma cell population in the bone marrow (BM). It is of particular interest that the tumor plasma cells appear to be restricted to the microenvironment of the BM and are rarely detected in the peripheral system, yet the disease is found widely disseminated throughout the axial skeleton. Furthermore, isolation of MM tumor cell lines has proven to be quite problematic due to their slow growth rate. These obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
126
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(132 citation statements)
references
References 42 publications
5
126
0
1
Order By: Relevance
“…21 Recent investigations have begun to elucidate from where in the B cell lineage the malignant myeloma clones originate. 27 On the basis of immunoglobulin and other gene sequences, B lymphocytes clonally related to malignant plasma cells have been identified in the bone marrow [28][29][30][31] and peripheral blood 28,30,[32][33][34][35][36][37] of myeloma patients. Myeloma cells, as well as these clonally related lymphocytes, express immunoglobulin genes that have undergone somatic hyper-mutation, reflecting antigen exposure.…”
Section: Monoclonal Gammopathy and The Progression To Myelomamentioning
confidence: 99%
See 2 more Smart Citations
“…21 Recent investigations have begun to elucidate from where in the B cell lineage the malignant myeloma clones originate. 27 On the basis of immunoglobulin and other gene sequences, B lymphocytes clonally related to malignant plasma cells have been identified in the bone marrow [28][29][30][31] and peripheral blood 28,30,[32][33][34][35][36][37] of myeloma patients. Myeloma cells, as well as these clonally related lymphocytes, express immunoglobulin genes that have undergone somatic hyper-mutation, reflecting antigen exposure.…”
Section: Monoclonal Gammopathy and The Progression To Myelomamentioning
confidence: 99%
“…Myeloma cells, as well as these clonally related lymphocytes, express immunoglobulin genes that have undergone somatic hyper-mutation, reflecting antigen exposure. 27,30,31,36,38,39 Ongoing hypermutation does not occur during tumor progression. 39 Thus, transformation occurs after somatic hypermutation, and the lack of subsequent mutation indicates that the malignant, clonal lymphocyte-plasma cell population has escaped the antigen selection process.…”
Section: Monoclonal Gammopathy and The Progression To Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…The B-cell nature of myeloma 'stem' cells was addressed when it was shown that myeloma-related clonotypic B cells exist in patients with MM (Billadeau et al, 1993;Rasmussen et al, 2004). It is well known that memory B-cells are biased toward plasma cells: once memory B cells are activated, they enter the cell cycle, and most begin differentiation into plasmablasts and then plasma cells, while some exit the cell cycle and remain at the B-cell stage (Jégo et al, 2001).…”
mentioning
confidence: 99%
“…5,6 Clonotypic B cells have been demonstrated in autologous blood/bone marrow stem cells in MM [7][8][9][10][11] and a correlation between autografting with heavily contaminated material and relapse has been suggested in MM and other diseases. 9,12 Purging of transplant material to reduce malignant contamination may involve treatment of patients either by radiation, chemical or immunological means prior to collection of autologous cells in order to achieve an in vivo purging effect.…”
mentioning
confidence: 99%